Tārīkh al-Maghrib al-ʿArabī : Lībyā wa-Tūnis wa-al-Jazāʾir wa-al-Maghrib min al-fatḥ al-ʿArabī ḥattá qiyām duwal al-Aghālibah wa-al-Rustumīyīn wa-al-Idārisah - ʿAbd al-Ḥamīd, Saʿd Zaghlūl (Dār al-Maʿārif, 1965)
A history of Libya, Tunisia, Algeria and Morocco from the Arab conquest until the founding of the Aghlabid, Rustamid and Idrisid states.